Marine Collagen–Chitosan Composite from Fishery By-Products for Wound Dressing: Characterization and Antibacterial Activity - Rachman, Sitti Hardiyanti; Rizfa, Mila Safitri; Kusumo, Shanca; Sehroh, Syarifah Nafhastus; Atqia, Iskarimah; Hidayat, Rachmat; Sinulingga, Fahri (Trends in Sciences, 2026)
Fishery by-products represent a sustainable source of marine biomaterials with significant potential for wound dressing applications. This study investigates a marine collagen–chitosan composite derived from Spanish mackerel skin and blue swimming crab shells as a candidate wound dressing material, with a focus on structural characterization and antibacterial activity. Acid-soluble collagen (ASC) was extracted through alkaline pretreatment followed by acetic acid hydrolysis, yielding 3.125%, and the freeze-dried product exhibited a porous white morphology with well-preserved amide bands. SEM–EDX analysis revealed a distinct transformation from the dense dermal matrix of raw skin to a layered ASC structure dominated by carbon and oxygen elements, indicating improved collagen purity. Chitosan obtained from blue swimming crab shells achieved a 19.3% yield, moderate viscosity (65.3 mPa·s), and a high degree of deacetylation (92.57%). FTIR and EDX characterization confirmed the successful removal of acetyl groups and a substantial reduction in mineral elements. Antibacterial assays demonstrated that pure chitosan exhibited inhibitory activity against Escherichia coli (18.23 ± 0.20 mm) and Staphylococcus aureus (15.80 ± 1.65 mm), while collagen–chitosan composites retained activity against E. coli but showed reduced effectiveness against S. aureus. These results demonstrate the feasibility of utilizing locally derived marine collagen and chitosan as a composite biomaterial, with antibacterial performance influenced by chitosan proportion and requiring further formulation optimization. HIGHLIGHTS Marine by-products were valorized into collagen and chitosan, providing a sustainable source for biomaterial development. The extracted chitosan exhibited a high degree of deacetylation (92.57%), enhancing its functional and antimicrobial potential. A porous fibrillar collagen structure with preserved functional groups was observed, supporting its suitability for wound dressing applications. Pure chitosan exhibited effective antibacterial activity, particularly against coli. Collagen–chitosan composites showed reduced antibacterial performance, highlighting the need for formulation optimization. GRAPHICAL ABSTRACT